The Mediation Role of Shopping Lifestyle and Moderation Role of Payletter on the Impact of Hedonic Shopping Motivation on Implicit Buying - Yosanda Zata Aman; Diah Widiawati; Dwicahya Setia Putri (Syntax Idea, 1977)
The purpose of this study is to examine how hedonic shopping incentive affects implicit purchasing behavior and how pay letters and shopping lifestyles mediate that effect. This study was conducted on customers of e-commerce users in Indonesia who also used paylater payment methods for their online shopping transactions. The study involved 213 customers as samples. Research data is collected using a questionnaire and the results are analyzed using PLS software. This research is quantitative. The findings showed that hedonic shopping motivation had a significant positive impact on impulsive buying and shopping lifestyles as well as shopping lifestyle had significant positive influence on impulse baying. The mediation test in this initiation showed that shopping lifestyle mediates the influence of hedonic shopping motivation on impulsive buying. However, on the other hand, the role of moderators paylater on the influence of hedonic shopping motivation against impulsive buying in reversal or paylatter does not play a role in moderating the influences of hedonical shopping motivations against impulsively buying.